2005
DOI: 10.1016/j.jpsychires.2005.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid status influences the volume of the rat cingulate cortex – a magnetic resonance imaging study

Abstract: Imbalances in the corticosteroid milieu result in reductions in hippocampal volume in humans and experimental rodents. The functional correlates of these changes include deficits in cognitive performance and regulation of the hypothalamic-pituitary-adrenal axis. Since other limbic structures which are intricately connected with the hippocampal formation, also play an important role in behavioural and neuroendocrine functions, we here used magnetic resonance imaging (MRI) to analyse how two of these areas, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
60
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 53 publications
(56 reference statements)
9
60
2
3
Order By: Relevance
“…In line with this hypothesis, a study of ACC volume in adults has shown an inverse correlation with number of stressful or traumatic adverse childhood events (50). There is also a mechanism in place to explain how environmental stressors may alter ACC anatomy; stress induces the release of glucocorticoids, which have been shown to mediate structural alterations of the medial prefrontal cortex (51)(52)(53). It is possible that these structural changes reflect a shift in the activity of neural systems that acts to favor increased vigilance and heightened reactivity to negative emotional stimuli.…”
Section: Discussionmentioning
confidence: 94%
“…In line with this hypothesis, a study of ACC volume in adults has shown an inverse correlation with number of stressful or traumatic adverse childhood events (50). There is also a mechanism in place to explain how environmental stressors may alter ACC anatomy; stress induces the release of glucocorticoids, which have been shown to mediate structural alterations of the medial prefrontal cortex (51)(52)(53). It is possible that these structural changes reflect a shift in the activity of neural systems that acts to favor increased vigilance and heightened reactivity to negative emotional stimuli.…”
Section: Discussionmentioning
confidence: 94%
“…Both stress and GC can induce neurodegenerative changes in the hippocampus and PFC. 23,[40][41][42][43][44][45] These brain regions express GRs; 46 they are important for cognition and are affected early in the development of AD. 47 Clinical reports of hypercortisolism in a significant number of AD patients 18,19 suggest a causal role for GC in AD, a view supported by studies in laboratory rodents that have shown that GC participate in the regulation of APP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Please note that during the production process errorsmaybe discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. (Cerqueira et al, 2005a, Cerqueira et al, 2005b. …”
mentioning
confidence: 99%
“…dexamethasone (DEX) reduces anterior cingulate cortex volume through dendritic atrophy (Cerqueira et al, 2005a, Cerqueira et al, 2005b.…”
mentioning
confidence: 99%